Yoga sebagai Upaya Mengurangi Nyeri Haid pada Remaja di Sekolah MTS Nurul Islam - Anggun Puspita Dewi; Nurul Firdaus; Tuti Emawati; Nurjanah; Risma Aliviani Putri (Universitas Ngudi Waluyo, 2025)
Menstrual pain (dysmenorrhea) is a common complaint among adolescent girls and can disrupt comfort and learning activities at school. Many adolescents experience abdominal cramps, back pain, headaches, and mood changes, yet few are aware of effective non- pharmacological management methods. Yoga is a form of physical exercise and relaxation that can help relieve menstrual pain through muscle stretching, breathing, and body relaxation (Rong et al., 2020). Objective: This community service activity aims to provide reproductive health education and train adolescent girls at MTs Nurul Islam to perform yoga movements to safely and independently reduce menstrual pain intensity. Methods: The activity was conducted on December 13, 2025, with 34 female students from grades VII–IX experiencing menstrual pain. The implementation included a pre-test, education on menstrual pain and the benefits of yoga, guided yoga practice with an instructor, and a post-test to assess participants’ knowledge and skills improvement. Results: Pre-test results showed that most participants had adequate knowledge of menstrual pain and yoga. After the educational and yoga practice sessions, post-test results indicated a significant improvement, with 76% of participants having good knowledge and all participants able to perform yoga movements correctly. Participants also reported reduced menstrual pain intensity and increased comfort during school activities. Conclusion: Yoga is proven effective as a non-pharmacological method for reducing menstrual pain in adolescent girls while enhancing their understanding of reproductive health. This activity can be considered a safe, easy-to-practice, and beneficial intervention for the well-being of adolescent girls at school Abstrak Nyeri haid (dismenore) merupakan keluhan umum yang dialami remaja putri dan dapat mengganggu kenyamanan serta aktivitas belajar di sekolah. Banyak remaja mengalami kram perut, nyeri punggung, sakit kepala, dan perubahan suasana hati, namun masih sedikit yang mengetahui cara penanganan non-farmakologis yang efektif. Yoga merupakan latihan fisik dan relaksasi yang dapat membantu meredakan nyeri haid melalui peregangan otot, pernapasan, dan relaksasi tubuh (Rong et al., 2020). Tujuan: Kegiatan pengabdian masyarakat ini bertujuan memberikan edukasi kesehatan reproduksi dan melatih remaja putri di Sekolah MTs Nurul Islam melakukan gerakan yoga untuk mengurangi intensitas nyeri haid secara aman dan mandiri. Metode: Kegiatan dilaksanakan pada tanggal 13 Desember 2025 dengan peserta sebanyak 34 remaja putri kelas VII–IX yang mengalami nyeri haid. Metode pelaksanaan meliputi pre- test, edukasi tentang nyeri haid dan manfaat yoga, praktik gerakan yoga bersama instruktur, serta post-test untuk mengukur peningkatan pengetahuan dan keterampilan peserta. Hasil: Hasil pre-test menunjukkan sebagian besar peserta memiliki pengetahuan cukup mengenai nyeri haid dan yoga. Setelah kegiatan edukasi dan praktik yoga, hasil post-test menunjukkan peningkatan signifikan, dengan 76% peserta memiliki pengetahuan baik dan seluruh peserta mampu melakukan gerakan yoga secara benar. Selain itu, peserta melaporkan penurunan intensitas nyeri haid dan meningkatnya kenyamanan saat beraktivitas di sekolah. Kesimpulan: Yoga terbukti efektif sebagai metode non-farmakologis untuk mengurangi nyeri haid pada remaja putri, sekaligus meningkatkan pemahaman mereka tentang kesehatan reproduksi. Kegiatan ini dapat dijadikan alternatif intervensi yang aman, mudah dilakukan, dan bermanfaat bagi kesejahteraan remaja putri di sekolah.